DAMPAK PENGGUNAAN JANGKA PANJANG DARI KONTRASEPSI IMPLAN ETONOGESTREL: LITERATURE REVIEW: DAMPAK PENGGUNAAN JANGKA PANJANG DARI KONTRASEPSI IMPLAN ETONOGESTREL: LITERATURE REVIEW - Tarigan, Siang Br (WELL BEING, 2021)
Implantable contraceptives are a long-term birth control option for women. However, contraceptive implants are not suitable for everyone. One of the contraceptive implants that is often used is etonogestrel. Etonogestrel is a progestin, or synthetic progestogen, and is therefore an agonist of the progesterone receptor, the biological target of progestogens such as progesterone. It works by stopping ovulation, thickening the mucus around the cervical opening, and changing the lining of the uterus. It has very weak androgenic and glucocorticoid activity and no other important hormonal activity. The purpose of this study was to determine the side effects of long-term use of the etonogestrel implant contraceptive through a literature study. The three databases used are Pubmed, ScienceDirect, and Scopus in this study. The literature search was carried out after the PICO was determined and used the keywords “Effect”, “Etonogestrel Contraceptive Implant”, “Long Term”. Based on the analysis of the 11 articles obtained in this study, it can be concluded that the Etonogestrel Implant Contraceptive is a safe and effective contraceptive method for use in women of childbearing age. Even so, etonogestrel has side effects such as menstrual irregularities, breast tenderness, mood swings, acne, headaches, vaginitis